Ludo carbon compound board game to study chemistry form 5 - Stanley, Theresa (Academica Press Solutions, 2022)
Secondary school students in Form Five, taking the KSSM syllabus, study Carbon Compound in Chapter two. The chapter focuses on the five homologous groups' physical and chemical characteristics. Given the length and abstract concept of the content, a game board named Ludo Carbon Compound (LCCB) was developed using the theory of social constructivism, which encourages collaboration during learning. The board game is designed to have five rectangles, each representing the five homologous groups. All rules of the traditional Ludo game are retained except for the part where the students need to answer a question from the stack of game cards to enter a token into play from its yard to its starting square. Each student is given five tokens. Along the path, students who land in spaces labelled "C" are required to answer a question from the stack of question cards. Failing to respond will need them to move two steps back. Students will move the coloured token from the starting square and must move in a clockwise direction around the track given by the number thrown on a die. If a piece lands on a piece of a different colour, the piece jumped upon is returned to its starting square. If a piece lands upon a piece of the same colour, this forms a block. This block cannot be passed or landed on by any opposing piece unless they answer a question from the game cards. A piece can only be moved onto the home square by an accurate throw—the first person to move all four pieces into the home square wins. A survey on the perception and learning effectiveness was conducted on the 24 students who played the board game. The data collected from the study were analysed to show the effect of the board game on perception and learning effectiveness. Besides that, the relationship between gender and learning effectiveness was also investigated. LCCB can be marketed as there is no available board game in the market to study Carbon Compounds besides being an alternative 21st-century activity in the classroom.